Development of Slovene Grammar School and Position of Geography, the subject in the Grammar School Curriculum - Konečnik Kotnik, Eva (Journal for Geography, 2007)
After four grades elective grammar school was founded in 1958, the institution of grammar school has been a subject of frequent changes that repeatedly directly or indirectly reflected socio-political changes. Simultaneously with changes of grammar school as an institution, the position of geography as a subject in the curriculum has changed. Lessening of compulsory hours of geography has been followed from foundation of grammar school till today.